Da'wah Organization Development Strategy Through Organizational Culture - Iwan Koswara (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2020)
This study seeks to examine and analyze how the development of the Muhamadiyah Islamic organization, through the Organizational Culture that takes place in it. The study was conducted using a qualitative approach that took the locus of Muhammadiyah organization. The data was obtained through observation and study of literature from books, journals and sites that are relevant to the research topic.. The results showed that organizational Culture for members of the Muhammadiyah organization was an important matter of how they adapted themselves to the organization's environment engaged in the religious field and built their integrity and commitment to the organization. Organizational Culture is a reflection of the existence of the organization itself. What is reflected in organizational Culture is the beliefs, values, norms, to the behavior of the members of the organization that is concerned. Research has an impact on the development of theory and the development of Islamic da'wah organizations in a practical way in the life of public and nationality.Penelitian ini mengkaji dan menganalisis tentang strategi pengembangan organisasi Islam Muhamadiyah melalui Budaya Organisasi. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kasus, teknik pengumpulan data dilakukan melalui observasi, wawancara,  dan dokumentasi. Hasil penelitian menunjukkan bahwa, Budaya organisasi  bagi anggota organisasi Muhammadiyah merupakan hal penting dalam mengadaptasikan diri terhadap lingkungan organisasi yang bergerak dalam bidang keagamaan serta membangun integritas dan komitmen diri terhadap organisasi. Budaya organisasi merupakan refleksi dari keberadaan organisasi yang berkaitan dengan keyakinan, nilai, norma, hingga perilaku para anggota organisasi yang bersangkutan. Penelitian berdampak pada pengembangan teori dan pembangunan organisasi dakwah Islam secar praktis dalam kehidupan keummatan dan kebangsaan.